Prevalence, patterns and socio-demographic correlates of tobacco use in Davangere taluka, Karnataka: a community-based, cross-sectional study - Patil, Basanagouda K.; Patil, Vijay S.; Nagrajachari, A.; Kiran, D.; Patil, Sunita B. (International Journal Of Community Medicine And Public Health, 2020)
Background: Tobacco use is the single, largest preventable cause of death and disability worldwide. Area-specific community-based epidemiological studies on tobacco use are required to quantify the problem, identify the determinants and their distribution. The objectives were to find out the prevalence, patterns and socio-demographic correlates of tobacco use in Davangere taluka, Karnataka, India. Methods: This was a community-based, cross-sectional study of 2008 subjects (>10 years of age) in urban and rural areas of Davangere taluka, Karnataka. Interviews were conducted by using a structured, pre-tested questionnaire by house-house visits. Results are presented using percentages, chi-square test, odds ratio and multiple logistic regression analysis. Results: The prevalence of tobacco use was 30.7%. Among urban males it was 39.5%, rural males 39.6%, rural females 26% and urban females 18.5%. Tobacco use was significantly associated with sex, locality, religion, caste, marital status, family type, occupation, and tobacco use in family or friends. There was direct relationship of tobacco use with age and inverse relationship with education and socio-economic status. Mixed tobacco use was higher in rural areas compared to urban areas. About 73.9% of 10-29 years persons had started before the age of 18 years. Among older participants there was higher frequency of consumption and duration of use. Conclusions: Tobacco use is common and it is influenced by various local socio-demographic factors. Addressing these factors and providing tobacco cessation services should be included as key strategies in tobacco control.